(untitled) (Journal of Nepal Geological Society, 1996)
The Sub-Himalaya in the Bagmati River region of central Nepal consists of two groups of rocks very different in age and characters. The Bagmati Group, an assemblage of pre-Siwalik rocks are found within the Siwalik Group. The Bagmati Group consists of sedimentary rocks, metasediments and basic rocks. The Siwalik Group is divided into the Lower, Middle and Upper Siwaliks. The Upper Siwalik is further subdivided into the Gadhan Khola, Chiruwa Khola and Bhainse Khola Formations. Vertebrate fossils were found in the lower and middle part of the Upper Siwaliks. An index fossil identified as Elephas planifrons was discovered for the first time in this region from a massive sandstone bed belonging to the upper part of the Upper Siwaliks. A conglomerate horizon with predominantly Siwalik sandstone clasts occur at the uppermost level of the Siwalik Group exposed in the southern belt. They in turn are unconformably overlain by flat lying younger Dun gravels. The Sub-Himalayan rocks are distributed into the northern and the southern belts, separated by the Chaura-Marin Thrust. The northern belt is characterised by a number of thrusts and faults resulting in the cropping out of the Bagmati Group sediments and the repetition of the formations of the Siwalik Group. The southern belt shows largely north dipping sequences from the Lower to the Upper Siwaliks. Both the belts show plunging folds in the vicinity of the thrusts. Several NW-SE, NE-SW and N-S trending faults have cut across the entire Siwalik Range.